2022
DOI: 10.3390/su14159631
|View full text |Cite
|
Sign up to set email alerts
|

Reducing PAPR with Low Complexity Filtered NOMA Using Novel Algorithm

Abstract: Filtered Non-Orthogonal Multiple Access (F-NOMA) is a multi-carrier wave form and is considered a suitable contender for 5G radio. Peak to average power ratio (PAPR) is regarded as a major hurdle in the NOMA wave form because it hampers the efficiency of the power amplifier of the NOMA transmitter. In this study, a novel selective mapping (SLM) algorithm is used to minimize the PAPR of the NOMA. The conventional SLM increases the intricacy of the structure, and the projected SLM algorithm is applied to the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The power saving is related to the signal PAPR value, this measurement is important for the system transmission, the lower the PAPR value the higher power saving for the amplifier used, the power saving is defined as 49,50 :…”
Section: The Performance Over the Power Savingmentioning
confidence: 99%
“…The power saving is related to the signal PAPR value, this measurement is important for the system transmission, the lower the PAPR value the higher power saving for the amplifier used, the power saving is defined as 49,50 :…”
Section: The Performance Over the Power Savingmentioning
confidence: 99%
“…A unique SLM method is employed in Ref. [ 28 ] to reduce the PAPR of the NOMA. The projected SLM method is used for the transmitter portion of the F-NOMA, while the conventional SLM enhances the complexity of the structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is observed that the hybrid algorithm efficiently enhances the BER and PAPR performance with low computational intricacy. In reference, 16 the authors applied a novel SLM method to the filtering NOMA for different transmission schemes. It is seen that the proposed SLM efficiently obtains a gain of 1 dB and enhances the power performance of the amplifier.…”
Section: Literature Reviewmentioning
confidence: 99%